Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Fisika Melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) SMAN 1 Cikalongwetan - Yudi Nugraha; Supardi Supardi (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This study was motivated by the low learning outcomes of students in Physics subjects in class XII MIPA 7 at SMAN 1 Cikalongwetan, where most students had not reached the minimum mastery criteria. The purpose of this research was to improve student learning outcomes through the implementation of the Problem-Based Learning (PBL) model. The study employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of two meetings. Each cycle included planning, action, observation, and reflection stages. Data were collected through observations and written tests. The results showed an improvement in student learning outcomes after the implementation of the PBL model, as indicated by the increased number of students achieving scores above the minimum standard and a higher percentage of overall mastery. These findings suggest that the Problem-Based Learning model can be an effective solution to enhance student achievement in Physics. The implication of this study emphasizes the importance of the teacher’s role in designing student-centered learning and facilitating critical thinking and problem-solving skills.